A Cultural Conduct Risk Assessment Model for Embedding Ethical Governance in Financial and Insurance Sales Practices - Habeeb Olatunji Olawale,; Ngozi Joan Isibor,; Joyce Efekpogua Fiemotongha, (International Journal of Scientific Research in Science and Technology, 2024)
The integrity of financial and insurance institutions increasingly hinges on their ability to embed ethical governance within frontline sales practices. In response to widespread misconduct scandals and evolving regulatory expectations, this paper proposes a robust, metrics-based conduct risk assessment model designed to evaluate and reinforce ethical behavior across sales-driven environments. Unlike traditional compliance frameworks that focus narrowly on regulatory adherence, this model integrates cultural diagnostics, behavioral risk indicators, and ethics training effectiveness to form a holistic view of organizational conduct. Drawing from interdisciplinary literature in organizational behavior, ethics, and governance, the model introduces quantifiable indicators—such as whistleblower activity, customer complaint patterns, and training retention metrics—to assess cultural alignment and ethical maturity within teams. It also delineates data collection tools including behavioral surveys, digital activity analysis, and feedback loops to ensure real-time insight into frontline behavior. Further, the model is architected to align with compliance, HR, internal audit, and sales management, creating a cross-functional framework for ethical oversight. Through case applications in financial and insurance sectors, this paper demonstrates how the model can be used to evaluate sales conduct, detect mis-selling risks, and optimize ethics training. The study concludes by outlining strategic implications for firms and regulators, acknowledging implementation challenges, and proposing directions for future research, including AI integration and cross-cultural validation. This research contributes a novel, actionable framework for transforming ethical governance from a reactive obligation into a proactive driver of trust, performance, and regulatory resilience.
Keywords: Conduct Risk; Ethical Governance; Cultural Risk Assessment; Financial Sales Practices; Metrics-Based Compliance; Behavioral Risk Management